Fossil evidence for a Cretaceous rise of the mahogany family. Issue 1 (5th January 2020) - Atkinson, Brian A.
Abstract : Premise: The mahogany family (Meliaceae) is an angiosperm lineage comprising many species that are important elements in tropical ecosystems, and is often used as a study system to understand the evolution of tropical rainforests. While divergence time studies have estimated a Cretaceous origin for the family, no unequivocal fossils of that age have been described. Here, the first Cretaceous evidence for Meliaceae is reported, based on an exceptionally well‐preserved fruit from the Upper Cretaceous (79–72 Ma, Campanian) of North America. Methods: The fossil fruit was prepared using traditional paleobotanical techniques. Bayesian phylogenetic analyses using morphological and molecular data were conducted to assess the phylogenetic position of the Cretaceous fruit in Meliaceae and to assess the effect of morphology for inferring the overall pattern of phylogeny for the family. Results: The fruit consists of a fleshy mesocarp and a woody endocarp with a hollow center, nine locules, loculicidal sutures, and one subapically attached seed per locule that has an enlarged sarcotesta near the hilum. The combination of characters in this fruit is strikingly similar to the genus Melia L. Phylogenetic analyses recover the Cretaceous fruit as being closely related to Melia and highlights the effect of fruit morphological data for inferring the overall pattern of phylogeny in Meliaceae. There are a few structural differences between the fossil fruit of this study and Melia ; thus, the newly characterized Cretaceous taxon is named Manchestercarpa vancouverensis gen. et sp. nov. Discussion: These results clearly confirm a Cretaceous origin for Meliaceae and that important tropical families were present prior to the development of modern tropical ecosystems in the Cenozoic.